Elucidation of drug resistant mutations of Mycobacterium tuberculosis by whole genome sequencing from North India - Sethi, S; Hao, Y; Brown, S; Walker, T; Yadav, R; Zaman, K; Aggarwal, A; Behera, D (Elsevier, 2019)
INTRODUCTION:Rapid diagnosis of drug resistant tuberculosis is required for better patient management and treatment outcome. Whole-genome sequencing (WGS) can detect single nucleotide polymorphisms (SNPs) and deletions/insertions which are responsible for mostMycobacterium tuberculosis drug resistance. WGS is being performed at scale in high-income countries but there are still limited reports of its use in India. METHOD:In this study, 33 clinicalM. tuberculosis isolates were taken from Mycobacterial repository in Chandigarh and were whole-genome sequenced. Phenotypic drug susceptibility testing was performed according to WHO recommendations. Four were considered culture contaminated. RESULTS:Among the other 29 isolates, 21(72.4%) were multi-drug resistance (MDR-TB) and one was extensively-drug resistant (XDR-TB). The most common mutations observed for isoniazid, rifampicin, ofloxacin and kanamycin werekatG_S315 T, rpoB_S450 L, gyrA_A90 V and rrs_A1401 G respectively. The isolates belonged to lineage 2 and 3, with most MDR-TB among lineage 2 isolates. CONCLUSION:Whole-Genome Sequencing ofMycobacterium tuberculosis offers the detection of drug resistance to all drugs in a single test and also provides insight into the evolution and drug-resistant tuberculosis.